2011
DOI: 10.1002/uog.9042
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an objective method of image assessment for first‐trimester nasal bone

Abstract: Objective To evaluate the degree of agreement in firsttrimester nasal bone assessment in a group of sonographers before and after training, using a semi-quantitative scoring system. (ICC, 0.929). Methods ConclusionThe proposed scoring system can be used to improve consistency and reliability in first-trimester nasalbone assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 12 publications
(13 reference statements)
2
6
0
Order By: Relevance
“…Similar findings have been demonstrated in second‐trimester fetal biometry. Studies on NT and nasal bone measurements have also found objective assessment to be more reproducible than is subjective judgment.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Similar findings have been demonstrated in second‐trimester fetal biometry. Studies on NT and nasal bone measurements have also found objective assessment to be more reproducible than is subjective judgment.…”
Section: Discussionsupporting
confidence: 75%
“…All images were evaluated both subjectively and objectively by two independent reviewers (A and B). This was done using similar methodology to that used for studies assessing second‐trimester biometry and first‐trimester NT and nasal bone measurements. For subjective evaluation, the reviewers were required to rate an image as either acceptable or unacceptable when the image was presented to them.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For one sonographer (a), 3% of 365 triplicate measurements were above 97.5 th centile; for the other (b), 17% of 186 measurements were above accepted threshold, set at 10%, and retraining was undertaken. quality 7,10,23,24 , and secondly, visual assessment of ultrasound images was based on an objective criterion-based scoring system, which has been shown to be significantly more reproducible than subjective methods 8,25,26 . In Salomon et al's 8 original description of this process, high reproducibility levels for the image scoring method were demonstrated (kappa between 0.60 and 0.98); despite undertaking QC in a blinded fashion, the results from our study were even better.…”
Section: Discussionmentioning
confidence: 99%
“…This shows that nasal bone is an essential marker for improved screening efficacy. We have recently demonstrated good consistency in its assessment amongst our sonographers and that further improvement can be achieved with appropriate training [15]. …”
Section: Discussionmentioning
confidence: 99%